CIRCULAR ECONOMY AND SUPPLY CHAIN: A SCIENTIFIC CHARACTERIZATION - Pereira, Renan; Ferreira, Edivan Alexandre; Alves, Josivan Leite; de Nadae, Jeniffer; Galvão, Graziela Darla Araujo (Brazilian Journal of Operations & Production Management, 2020)
Goal: To analyze the publications on circular economy and supply chain using a systematic review of the literature and bibliometric analysis, the study was designed to answer the question: How is the international scientific production about Circular Economy and Supply Chain characterized? For such an answer it was found that the first published article was on the subject date from 2006 and 2013 there was a steady increase in the number of publications. Many publications mentioned the use of CE in the supply chain through the management of the green supply chain. The country with more publications about the area in the United Kingdom with 19,1% of papers. Moreover, publications are generally about IT product and service supply chains. Design/Methodology/Approach: Systematic literature review based on bibliometric theory and social network analysis, linking Circular Economy and Supply Chain. Results: The articles do not point to studies on a specific supply chain, but only stress the importance of applying Circular Economy to the supply chain to mitigate the environmental impact of materials and products along with the flow from the production process to end consumers. Limitations of the investigation: This paper contributes by analysing the international literature about the selected topics. In a future research agenda, this study could be applied to survey-based research to answer the research propositions suggested. Practical implications: The research helps scholars to identify the main hot topics about Circular Economy and Supply Chain, main authors and papers. Also, can help managers to develop Circular Economy business models to improve and mitigate the environmental impacts on the production and supply chain. Originality / Value: This research sheds light on controversies, discussed in the literature, concerning the effects linking Circular Economy and Supply Chain.